Lynn Hershman Leeson: Civic Radar. - RUBIN, NATHANIA (Afterimage)
The article reviews the exhibit "Lynn Hershman Leeson: Civic Radar," on view at the ZKM Center for Art and Media in Karlsruhe, Germany from December 13, 2014 to April 6, 2015.